The Literary And Linguistic Role Of Ghazals In Furkat's Literary Heritage (Zien Journal of Social Sciences and Humanities, 2022)
This article examines the literary and linguistic role of the ghazal genre in Furkat's literary heritage. It was studied that Furkat's poems continue the traditions of classical literature, that the poet brought a new, modern spirit to the genre, and that elements of the Uzbek language were used effectively in them.